"Facilitation of Stereoscopic Depth Perception by a Relative-Size Cue in Ambiguous Disparity Stereograms": Erratum - Fineman, M.B. (Journal of Experimental Psychology, 1972)
Reports an error in the original article by Mark B. Fineman (Journal of Experimental Psychology, 1971[Oct], 90[2]], 215-221). Fig. 1 and Fig. 2 on pp. 216 and 217 were shown inverted. This mistake made it appear that Stimulus 1 was Stimulus 2, and that Stimulus 3 was Stimulus 4, and that the four stimuli were upside down. (The following abstract of this article originally appeared in record.) Proposed that the cue of relative size may facilitate depth perception in accordance with a crossed or uncrossed disparity in stereograms in which both tendencies are equally represented. A concurrent concept was that the latency associated with the perception of depth in random-dot stereograms may be due, in part, to a cue conflict between binocular disparity and relative size. 4 male and 2 female graduate students were given 8 presentations of 5 stereographic stimuli, in which disparity was ambiguous but relative size was systematically altered. Ss were tested for direction of depth preferences and response latency. Both the relative-size effects and an uncrossed disparity bias were evidenced in the data. The latter effect was attributed to binocular rivalry between dissimilar elements in the stereoscopic half-fields. It is concluded that depth cue relationships are more complex than had been suggested by simple dominance theories. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1972 American Psychological Association.
Keywords: ambiguous disparity stereograms; dept.psy; relative size cue; stereoscopic depth perception facilitation

Drug abuse and television viewing patterns - Brodlie, Jerome F. (Psychology, 1972)
Keywords: dept.psy; ⛔ No DOI found

The effectiveness of a sex education program on the teacher's sex knowledge and attitudes - Karas, Shawky F; Elliot, Gale Ann (Small Group Research, 1972)
Keywords: dept.psy

The influence of communicator-recipient similarity upon the beliefs and behavior of pregnant women - Mazen, Ragaa; Leventhal, Howard (Journal of Experimental Social Psychology, 1972)
A field experiment was conducted to investigate the effects of communicator-recipient similarity and verbal communication upon the attitudes and behavior of pregnant women. Similarity was varied on two dimensions, pregnancy and color; and these factors were crossed with three communication conditions: (1) information on the advantages of rooming-in and breast feeding; (2) information combined with personal endorsement; and (3) no-information control. Both a pilot study and the main experiment showed no important differences in the amount of attitude change or behavioral compliance between the communication conditions. There were also no significant differences in attitude change as a function of similarity in pregnancy. However, a significantly higher proportion of mothers breast fed and roomed-in when the communicator was pregnant and similar than when she was nonpregnant and dissimilar. Similarity in color had no effect upon attitudes or behavior for the topic of rooming-in. But when the communicator was dissimilar in color there was significant negative change in attitudes toward breast feeding. Similarity in color also increased breast feeding. Attitudes and actions were related; mothers with initially favorable attitudes were more likely to comply for both issues. But with only one exception, attitude change was unrelated to behavioral compliance. The results are discussed in terms of visible similarity as a source of information or cues for action. © 1972.
Keywords: dept.psy